Relation of Descriptor Completeness and Distinctiveness to Localization of the Most Informative Regions in Images. (August 2015) - Kalinin, Konstantin B.; Petrushan, Mikhail V.; Samarin, Anatoly I.
Allocation of informative regions in images depends on a visual task. We propose two criteria for allocation of informative regions in images considering visual recognition of objects in images using a space-variant foveal filter. The first criterion relates to descriptor completeness. This criterion is formalized as a measure of similarity of an original image to an image reconstructed from foveal filter responses. The second criterion relates to descriptor distinctiveness. This criterion relates to the problem of retrieving discriminative and repeatable features in images of objects. It is formalized as a variation of descriptor elements of different objects within the same class. We reveal that regions of interest produced by these criteria are distributed in the areas of high variety of brightness gradients orientations.